Transarterial chemoembolization in the treatment of primary and recurrent pelvic tumors with peritoneal involvement: what results can be expected? - E. A. Zvezdkina; A. G. Kedrova; D. P. Lebedev; T. A. Greyan; D. N. Panchenkov; Yu. A. Stepanova (ABV-press, 2022)
Transarterial chemoembolization (TACE) with drug-saturated microspheres is used in the treatment of women with pelvic tumors complicated by bleeding. Another serious problem is peritoneal carcinomatosis. However, it has not been studied whether TACE affects peritoneal lesions, is there a difference in peritoneal lesions with primary and recurrent tumors? The purpose of this article is to analyze the results of TACE in women with peritoneal lesions with primary and recurrent pelvis tumors. This is an analysis of 80 patients with primary tumors (group 1) and 20 patients with recurrent tumors of pelvis (group 2). 8 women in group 1 and 11 women in group 2 had an implantation lesion of peritoneum near the main focus, 3 women in group 1 and 4 women in group 2 had a peritoneum lesion at a distance from the main focus. Angiography revealed differences in blood supply of implantation metastases in the group of primary and recurrent tumors, as well as the blood supply of distant peritoneal metastases. These facts should be taken into account in order to reduce the number of errors in assessing the effectiveness of therapy, to obtain a good clinical result, and to avoid discrediting TACE due to unreasonable requirements for it.